Desequilíbrio cambial e crescimento econômico: uma análise empírica baseada no modelo Balassa-Samuelson - Sampaio, Danilo Macedo Santos (2008)
Most empirical approaches only use productivity differentials to estimate the Balassa-Samuelson effect. Despite of that, the Balassa-Samuelson model assumes some important hypotheses that are generally ignored. Initially, this work intends to estimate the Balassa-Samuelson effect relaxing the hypothesis that the productive sectors (tradables and non-tradables) have the same relative size in all the countries. Following Rodrik (2007), a real exchange rate disequilibrium index is computed using the results of the Balassa-Samuelson effect estimation. After that, I estimate the effect of real exchange rate misalignment on economic growth and verify if Rodrik´s conclusions still hold.